2006
DOI: 10.1097/00008877-200609000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on 3-nitropropionic acid-induced biochemical and behavioural changes: possible neuroprotective mechanisms

Abstract: Huntington's disease is a progressive, degenerative disease characterized by abnormal body movements called chorea, and a reduction of various mental abilities. 3-Nitropropionic acid, an inhibitor of complex II of the electron transport chain, causes Huntington's disease-like symptoms in rodents. Recently, it has been reported that oxidative stress, which is one of the pathological hallmarks of various neurodegenerative disorders, also plays an important role in the pathogenesis of Huntington's disease. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 35 publications
7
82
0
3
Order By: Relevance
“…Intriguingly, systemic treatment with Ppt for 5 days restored the weight loss and mitigated the behavior disorders in the 3-NP treated rats. Kumar et al have shown that antioxidative treatments restore behavioral disorders and antioxidative defense mechanisms in 3-NP treated animals [10,11,31] . In the CNS, cells are able to defend against oxidative stress using several resources, including vitamins, bioactive molecules, lipoic acid, enzymes (such as SOD, GSH, GPx, HO-1, and NQO1), and redox sensitive protein transcription factors (such as AP-1, Nrf2, and HSF) [32,33] .…”
Section: Wwwchinapharcom Gao Y Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, systemic treatment with Ppt for 5 days restored the weight loss and mitigated the behavior disorders in the 3-NP treated rats. Kumar et al have shown that antioxidative treatments restore behavioral disorders and antioxidative defense mechanisms in 3-NP treated animals [10,11,31] . In the CNS, cells are able to defend against oxidative stress using several resources, including vitamins, bioactive molecules, lipoic acid, enzymes (such as SOD, GSH, GPx, HO-1, and NQO1), and redox sensitive protein transcription factors (such as AP-1, Nrf2, and HSF) [32,33] .…”
Section: Wwwchinapharcom Gao Y Et Almentioning
confidence: 99%
“…Antioxidative drugs [20] and the overexpression of genes involved in attenuating oxidative stress showed significant neuroprotective effects against 3-NP-mediated neurotoxicity [11,31] . Ppt warrants attention as a potential anti-oxidative therapy for HD.…”
Section: Wwwchinapharcom Gao Y Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, a plant-derived phytoestrogen, may minimise the deterioration in cognitive function associated with physical and chemical damage to the brain [1][2][3][4][5][6][7]. In rats and mice, resveratrol has been found to minimise the adverse brain and cognitive changes induced by neurologically damaging events such as streptozotocin-induced diabetes [1]; percussive cerebral trauma [2]; focal cerebral ischemia (stroke) [3]; oxidative stress caused by intracerebroventricular injection of streptozotocin [4] or cochinine [5]; and neurotoxic substances used to mimic Huntington's disease [6] and Parkinson's disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major mechanisms of toxin action is the induction of mitochondrial dysfunction via oxidative stress. Several studies reported the protection activity of resveratrol against this neurotoxin and suggested that it was its antioxidant properties that are responsible for the prevention of the functional effect of the toxin (Binienda et al, 2010;Kumar et al, 2006). Furthermore, some authors reported that the beneficial effect of resveratrol is through activation of SIRT1 (Howitz et al, 2003;Lagouge et al, 2006).…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%